Synthesis, XRD, spectral (IR, UV–Vis, NMR) characterization and quantum chemical exploration of benzoimidazole‐based hydrazones: A synergistic experimental‐computational analysis. (19th August 2019) - Rafiq, Muhammad; Khalid, Muhammad; Tahir, Muhammad Nawaz; Ahmad, Muhammad Umair; Khan, Muhammad Usman; Naseer, Muhammad Moazzam; Braga, Ataualpa Albert Carmo; Muhammad, Shabbir; Shafiq, Zahid
Abstract : Present study advocates the joint experimental and computational studies of two potent benzoimidazole‐based hydrazones with chemical formula C23 H18 F2 N4 O (5a ) and C25 H22 FN5 O3 (5b ). Both 5a and 5b were synthesized and resolved into their crystal structures using SC‐XRD for the assessment of bond lengths, bond angles, unit cells and space groups. The structures of 5a and 5b were chemically characterized using infrared (FT‐IR), UV–Visible, nuclear magnetic resonance ( 1 H‐NMR and 13 C‐NMR), EIMS and elemental analysis. DFT at M06‐2X/6‐31G(d, p) level of theory was performed to get optimized structures and countercheck the experimental findings. Overall, DFT findings show excellent concurrence with the experimental data which confirms the purity of both compounds. FMO, NBO analysis, MEP surfaces and nonlinear optical (NLO) properties were explored at same level of theory. UV–Vis analysis at TDDFT/M06‐2X/6‐31G(d, p) level of theory showed that 5b is red shifted with λ max 331.69 nm as compared to 5a with λ max 240.25 nm. Global reactivity parameters were estimated using energy of FMOs indicated the greater harness value than the softness values of 5a and 5b . NBO analysis confirmed that the presence of non‐covalent interactions, hydrogen bonding and hyper conjugative interactions are pivotal cause for the existence of 5a and 5b in the solid‐state. NLO results of 5a and 5b were observed better than standard molecule recommended the NLO activity of said molecules for optoelectronic applications. Abstract : Present study advocates the joint experimental and computational studies of two potent benzoimidazole‐based hydrazones with chemical formula C23H18F2N4O (5a) and C25H22FN5O3(5b). Both compounds were characterized using SC‐XRD, FT‐IR, UV‐Visible, 1H‐NMR, 13CNMR, and EIMS. Additionally, density functional theory (DFT) calculations were performed to countercheck the experimental findings and to explore the electronic as well as nonlinear optical (NLO) properties. This synergistic experimental‐computational study may provide new ways for utilization of 5a and 5b as NLO material for optoelectronic applications. Highlights: Two novel benzoimidazole‐based hydrazones were synthesized. XRD, NMR, FT‐IR, UV‐Vis, EIMS and elemental analysis were performed for the characterization. Computational study was done at M06‐2X/6‐31G(d, p) level for comparative study. Comparative study reveals a good agreement between experimental and DFT results. FMO, NLO and NBO analysis were performed.